Wielkość osoby i dzieła pastora Valeriusa Herbergera w świetle jego przydomków - Kalbarczyk, Adam (Poznańskie Studia Teologiczne, 2018)
Many attempts have been made to describe the life, fame and fate of the great German Luthe- ran pastor, preacher, theologian, humanist, poet, composer of well-known church songs and social activist, Valerius Herberger (1562-1627), who lived and worked in the Polish royal city Wschowa. The excellence of this gure has been proved by ample theological and homiletic works published in print. This article depicts the richness of both Herberger as a person and his works by making references to as many as ten bynames given to him. The rst three of them were coined by drawing an analogy to the father of the Reformation, Martin Luther, namely „the little Luther”, „the other Luther”, „the Polish Luther”. In two other epithets: „evangelical Abraham a Sancta Clara” and „the other Ignatius Loyola” Herberger was compared respectively to two gures well-known in the Catholic world, that is to an Augustinian Friar Abraham a Sancta Clara, one of the most famous, early baroque preachers, and to Ignatius Loyola, the founder of the Jesuits. The remaining ve bynames refer directly to Herberger’s performance as a preacher and a pastoral worker, that is: „Preacher of Jesus”, „Lover of Jesus”, „Preacher of the Heart”, „Warden of Hearts” and „Pastor of the Plague”. All those epithets pose a constant challenge to successive generations of preachers, theologians, priests, Catholic writers and social activists to become if not another Herberger, at least a little Herberger.